2011
DOI: 10.1021/ja206095a
|View full text |Cite
|
Sign up to set email alerts
|

Emissive RNA Alphabet

Abstract: A fluorescent ribonucleoside alphabet, comprised of highly emissive purine (thA, thG) and pyrimidine (thU, thC) analogs, all derived from thieno[3,4-d]pyrimidine as the heterocyclic nucleus, is described. Structural and biophysical analyses demonstrate that the emissive analogs are faithful isomorphic nucleoside surrogates. Photophysical analysis establishes that the nucleosides offer highly desirable qualities, including visible emission, high quantum yield and responsiveness to environmental perturbations, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
229
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(235 citation statements)
references
References 43 publications
5
229
0
1
Order By: Relevance
“…[1][2][3] Recently, a fluorescent guanine analogue, 2-aminothieno [3,4-d]pyrimidine ( th G), was developed. 4 One of the essential criteria of a successful analogue is to minimize the structural and functional disturbances when replacing any native residue. Along with many structural, photochemical, and biophysical characteristics, the acid dissociation constant, pK a , would be an important parameter to be monitored, particularly when an aqueous solution is used in the assay because pKa value is related to the stability of nucleic base, Watson-Crick base pairing, proton migration, and the mispair formation during the DNA replication.…”
mentioning
confidence: 99%
“…[1][2][3] Recently, a fluorescent guanine analogue, 2-aminothieno [3,4-d]pyrimidine ( th G), was developed. 4 One of the essential criteria of a successful analogue is to minimize the structural and functional disturbances when replacing any native residue. Along with many structural, photochemical, and biophysical characteristics, the acid dissociation constant, pK a , would be an important parameter to be monitored, particularly when an aqueous solution is used in the assay because pKa value is related to the stability of nucleic base, Watson-Crick base pairing, proton migration, and the mispair formation during the DNA replication.…”
mentioning
confidence: 99%
“…Pour atteindre cet objectif, nous avons utilisé deux analogues fluorescents de nucléosides très innovants, la 2-thiényl-3-hydroxychromone (3HCnt) capable de substituer toutes les nucléobases de l'ADN [7] et la thiénoguanosine (thG) qui remplace parfaitement la guanine [8,9]. En incorporant la 3HCnt ou la thG à des positions choisies d'un ADN double brin hémi-méthylé ou non méthylé, nous avons montré par spectroscopie de fluorescence qu'il était possible de suivre de manière sensible et fidèle le basculement des cytosines méthylées, induit par le domaine SRA de la protéine UHRF1 (Figure 2).…”
Section: Dnmt1unclassified
“…Recently, Tor and coworkers developed isomorphic fluorescent RNA nucleosides derived from thieno [3,4-d]-pyrimidine and reported that the nucleosides have important photophysical properties including visible light emission and a high quantum yield. 22 In addition, they have showed the usefulness of the nucleoside analogues in various applications. 2329 We have taken note of the potential of isomorphic nucleoside analogues based on a thieno [3,4-d]pyrimidine core and exploited the emissive DNA nucleoside analogues.…”
mentioning
confidence: 99%
“…22,37,38 The fluorescent base This glycosylation reaction yielded a mixture of β-and α-anomer at a β:α ratio of 3:2. After the benzoyl protecting groups of the deoxyribonucleoside 4 were removed in aqueous ammonia, the 5¤-hydroxy group of the nucleoside analogue 5 was protected with dimethoxytrityl ether (DMTr), and the desired β-anomer was isolated in 27% yield by column chromatography.…”
mentioning
confidence: 99%
See 1 more Smart Citation